2015
DOI: 10.1155/2015/902708
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mind-Body Interventions on Sleep Quality: A Systematic Review

Abstract: Study Objectives. To evaluate the effect of mind-body interventions (MBI) on sleep. Methods. We reviewed randomized controlled MBI trials on adults (through 2013) with at least one sleep outcome measure. We searched eleven electronic databases and excluded studies on interventions not considering mind-body medicine. Studies were categorized by type of MBI, whether sleep was primary or secondary outcome measure and outcome type. Results. 1323 abstracts were screened, and 112 papers were included. Overall, 67 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 129 publications
5
85
0
1
Order By: Relevance
“…The SF-36 Vitality subscore has also improved from a different mind-body intervention, yoga, in healthy older adults (Oken et al, 2006) and in people with multiple sclerosis (Oken et al, 2004). One self-report measure that did not improve was subjective sleep quality (PSQI), even though there is some evidence that mind-body medicine may improve sleep (Neuendorf, Wahbeh, Chamine, et al, 2015). While our study participants were not recruited for sleep problems, their average PSQI score at baseline was 8.4 (scores of 5 and above are considered “poor sleep quality”).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SF-36 Vitality subscore has also improved from a different mind-body intervention, yoga, in healthy older adults (Oken et al, 2006) and in people with multiple sclerosis (Oken et al, 2004). One self-report measure that did not improve was subjective sleep quality (PSQI), even though there is some evidence that mind-body medicine may improve sleep (Neuendorf, Wahbeh, Chamine, et al, 2015). While our study participants were not recruited for sleep problems, their average PSQI score at baseline was 8.4 (scores of 5 and above are considered “poor sleep quality”).…”
Section: Discussionmentioning
confidence: 99%
“…The Pittsburgh Sleep Quality Index (PSQI) (Buysse, Reynolds, Monk, Berman, & Kupfer, 1989) was administered because mind-body therapies improve sleep function (Neuendorf, Wahbeh, Chaime, et al, 2015) and may mediate stress effects on cognition (Oken, Fonareva, & Wahbeh, 2011a). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, studies have shown that meditation may be a useful adjunct to the treatment of mental health problems, particularly mood and anxiety disorders234. Evidence also suggests benefits of meditation for people suffering from physical conditions, including hypertension5, insomnia6, irritable bowel syndrome7 and symptoms related to epilepsy, premenstrual syndrome and menopause2. Importantly, meditation is considered to be a generally safe practice; while isolated reports suggest that meditation may aggravate some mental health problems8, the strength of this evidence is very low.…”
mentioning
confidence: 99%
“…A systematic review found positive evidence to suggest benefit of mind-body therapies for sleep especially in the elderly. 55 Research is limited on meditation’s impact in those with mild cognitive impairment (MCI) or dementia, but one small study showed that in adults with MCI, meditation positively impacted the regions of the brain most related to dementia. 56 Tai chi, a form of moving meditation, also has evidence for enhancing cognitive function, especially executive functioning, in older adults.…”
Section: Dementiamentioning
confidence: 99%